2015
DOI: 10.3390/ijms160716347
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Discovery of Genes Involved in Immune Pathways from Coelomocytes of Sea Cucumber (Apostichopus japonicus) after Vibrio splendidus Challenge

Abstract: Vibrio splendidus is identified as one of the major pathogenic factors for the skin ulceration syndrome in sea cucumber (Apostichopus japonicus), which has vastly limited the development of the sea cucumber culture industry. In order to screen the immune genes involving Vibrio splendidus challenge in sea cucumber and explore the molecular mechanism of this process, the related transcriptome and gene expression profiling of resistant and susceptible biotypes of sea cucumber with Vibrio splendidus challenge were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…At present, more and more studies on the immune system of the sea cucumber have been developed at both the molecular and cellular levels, which were based on the basal information for immune-related genes that provided by the transcriptomic studies [25]. However, the specific immune defense mechanism in the effector coelomocytes is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more and more studies on the immune system of the sea cucumber have been developed at both the molecular and cellular levels, which were based on the basal information for immune-related genes that provided by the transcriptomic studies [25]. However, the specific immune defense mechanism in the effector coelomocytes is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the applications of transcriptomic analyses in sea cucumber include identification of long noncoding RNA species [21], illustration of the mechanisms of aestivation [22], abnormal development [23], and body wall pigmentation [24]. Moreover, immune-related genes in the A. japonicus coelomocytes under Vibrio splendidus challenge have been identified, which are clustered into the immune pathways of endocytosis, lysosome, chemokine, and MAPK and ERBB signaling [25]. However, there is still limited research reports on the species and response of the cytokines secreted by coelomocytes of sea cucumber under challenge of immune stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Sandfish DMBT1 contains the canonical domains CUB, SRCR, and zona pellucida, which have been implicated in the mediation of protein-protein interactions 77 . DMBT1 has been suggested to be involved in host disease susceptibility and resistance 78,79 and in different developmental processes 80,81 . A natterin-like gene sharing similar domains (i.e., functionally uncharacterized DUF3421 superfamily and an aerolysin-like pore-forming domain) with naquin (Thalassophryne nattereri) natterins was also found to be differentially expressed in all hatchery datasets 82 .…”
Section: Deus Associated With Extracellular Regionmentioning
confidence: 99%
“…Because RNA‐Seq can survey the entire transcriptome in a very high‐throughput and quantitative manner (Yang, Zheng, Cui, Yang, & Chen, ), allowing an assessment of the complexity of the transcriptome and facilitating the identification of genes (Gao et al., ), this technology has been widely applied to uncover genes and pathways in microbes. In our previous study, we found that treatment with stresses (including Cu, Pb, Hg, and low pH) could reduce the adhesion of V. alginolyticus (ND‐01).…”
Section: Introductionmentioning
confidence: 99%